Dual Axes Solar Tracker - Ahmad Imran bin Ibrahim; Farah Diyana binti Abdul Rahman; Muazzin bin Rohaizat (Institute of Advanced Engineering and Science, 2018)
Photovoltaic (PV) is one of the most important sources of renewable energy in the world. Its current efficiency could be increased up to 60% by using dual axes solar tracker, which maximise PV exposure to sun. The most important component in dual axes solar tracker is sensing location of the sun. Four light dependent resistors (LDR) are used as the sensors, connected to potentiometers to increase their accuracy. Arduino UNO is used as the controller to control two stepper motors. Two experiments have been carried out, where the tolerance of the LDR has been found to be 0.05V and the calibration of the four LDRs to have the error of 0.03V. Both experiments proved the capability of LDR for dual axes solar tracker and potentiometer to increase their accuracy.